Review of research on tip-timing and tip clearance measurement technology - Liang ZHANG (Hebei University of Science and Technology, 2021)
Turbine blades will fail due to fatigue fracture caused by vibration at high-speed rotation,resulting in damage of rotating machinery.Blade tip-timing measurement technology is the most promising non-contact blade vibration real-time monitoring method at present,and the change of the blade tip clearance is closely related to the vibration state of the blade.Therefore,real-time monitoring of blade vibration state and blade tip clearance is the key to ensure the safe,stable,and reliable operation of rotating machinery.The principles and research results of blade tip-timing and blade tip clearance measurement technology in domestic and international were summarized.It was clarified that the current research is still in the incomplete maturity stage of simulation and experimental measurement,and the research prospects of blade tip-timing and blade tip clearance measurement technology were provided.It was pointed out that future research can be carried out in the following aspects: 1) combining blade tip-timing and tip clearance measurement technology to achieve blade vibration measurement;2) conducting asynchronous blade vibration measurement without the once per revolution (OPR) sensor method and putting it into engineering application;3) developing an effective dynamic calibration scheme to measure the relationship between the output voltage and the blade tip clearance when the blade is rotating;4) developing the sensors capable of high-precision and long-period measurements in harsh environments.[HQ]